The ’Jovem Arte Contemporânea’: on becoming an experimental and collaborative laboratory - Carreira, Lia (Opus Incertum, 2024)
The Jovem Arte Contemporânea (JAC), organized by the Museum of Contemporary Art of the University of São Paulo in Brazil (MAC USP) between 1967 and 1974, emerged from earlier debates on the new ideals of the modern museum. Under the rubric of the laboratory, it was transformed into a space of experimentation and collaboration. Among the editions, the 1971 and 1972 JACs were not only the most self-critical, but also, by focusing on matters of space and process, the most committed to challenging the foundations of its exhibition design and catalogue production. The following text recounts those pivotal transformations, highlighting the importance of the JAC’s catalogues to both artists and art historians, then and now, in establishing the sought-after ‘experimentality’ and ‘collaborativeness’ of its own exhibition spaces and practices.